Reactivity of the Insecticide Fenitrothion toward O and N Nucleophiles - Rougier, Natalia Mercedes (2010)
The reactivity of Fenitrothion (1) toward several O- and N-based nucleophiles, including ambident and alfa-nucleophiles, was investigated in basic media at 25ºC in water containing 2% 1,4-dioxane. In the reactions with HO- and HOO- quantitative formation of 3-methyl-4-nitrophenoxide (2) was observed indicating a SN2(P) pathway. In the reactions with NH2OH, NH2O-, and BuNH2, demethylfenitrothion (4) was formed along with 2, indicating competition between the SN2(P) and SN2(C) pathways; no evidence of a SNAr pathway was observed in any case. The observed rate constants were dissected into the values corresponding to the SN2(P) and SN2(C) pathways. The yield of 4 depends on the nucleophile and on the pH of the reaction, being the main product in the case of BuNH2. With HOO-, NH2OH, and NH2O- a significant alfa-effect was observed, confirming the participation of the nucleophile in the rate-limiting step of the reaction.